Porcelain Veneers in Vital vs. Non-Vital Teeth: A Retrospective Clinical Evaluation - Maciej Zarow; Louis Hardan; Katarzyna Szczeklik; Rim Bourgi; Carlos Enrique Cuevas-Suárez; Natalia Jakubowicz; Marco Nicastro; Walter Devoto; Marzena Dominiak; Jolanta Pytko-Polończyk; Wioletta Bereziewicz; Monika Lukomska-Szymanska (Bioengineering, 2023)
Nowadays, the ceramic veneer approach can be considered more predictable than direct composite veneer. To date, there is a lack of studies comparing the clinical performance of anterior veneers cemented on vital teeth (VT) and non-vital teeth (NVT). This longitudinal clinical study investigated the performance of ceramic veneers in VT or anterior NVT. A total of 55 patients were evaluated in the study. Two groups were defined based on the vitality status of the teeth (93 teeth—vital and 61 teeth—non-vital). The United States Public Health Service (USPHS) criteria were used to assess the clinical status. The data were evaluated statistically with the Mann–Whitney U test. All restorations were considered acceptable, and only one veneer in VT failed for the criteria of secondary caries. There were no statistically significant differences in any of the criteria evaluated (p ≤ 0.671). The ceramic veneers evaluated showed a satisfactory clinical performance both in VT and NVT.